Reforma del art. 108 del codigo civil ecuatoriano, violan los derechos garantizados en la Constitución de la Republica del Ecuador. Art. 11 numeral 3 - Chuquisala Carguaytongo, Carmen Yolanda (2015)
The consensual divorce is the process followed to terminate the marriage, in which husband and wife express loudly that it is his will, without any causes to proceed with the termination of marriage in which put an end to the reciprocal obligations arising from marriage, such as mutual support of the spouses. Within the constitutional legal framework specifically considered Article 11 paragraphs 3, 4, 5, 6, 9 and Article 75 which deals with the right of Ecuadorians to go for it that justice will be free and mainly guarantees speed procedural. The constitutional provisions regarding the right to freedom of expression arbitrarily violates the rules contained in Art. 108 of the Ecuadorian Civil Code which states that after a period of two months at the request of the spouses or their special prosecutors Judge of civil convene a conciliation hearing As the supreme law in Art. 11 paragraphs 3, 4, 6, 9 where we have the contradiction n Art. 108 of the Ecuadorian Civil Code mentioned procedure of divorce by mutual consent after a period of two months at the request of the spouses or its special prosecutors the civil judge will convene a conciliation hearing in which no express and manifest purpose contrary consumption and voice his final decision to give the marriage dissolved. Since the right of persons may be required to individually or collectively before competent authorities. The speed applies in all processes, whether these related to a procedure or specific standards, this, in the divorce by mutual agreement, where after accepted the demand is not met the judge in two months called to a hearing to convince the spouses, divorce is not the solution, made it stops the process, and that has no basis because the decision is made that many times, do not want the real causes they find involving spouses to make this decision, and see the special procedure for a way to legalize their marriage breakdown Everything mentioned in previous lines, set up in legal problems, which should be studied, in order to propose an alternative solution to avoid it and this forms a right of due process is violated.